2013
DOI: 10.5194/acp-13-1797-2013
|View full text |Cite
|
Sign up to set email alerts
|

Using the significant dust deposition event on the glaciers of Mt. Elbrus, Caucasus Mountains, Russia on 5 May 2009 to develop a method for dating and "provenancing" of desert dust events recorded in snow pack

Abstract: Abstract. A significant desert dust deposition event occurred on Mt. Elbrus, Caucasus Mountains, Russia on 5 May 2009, where the deposited dust later appeared as a brown layer in the snow pack. An examination of dust transportation history and analysis of chemical and physical properties of the deposited dust were used to develop a new approach for high-resolution "provenancing" of dust deposition events recorded in snow pack using multiple independent techniques. A combination of SEVIRI red-green-blue composi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 50 publications
2
28
1
Order By: Relevance
“…The 700 hPa vector wind fields serve as a good indicator of potential dust transportation to the Caucasus (Shahgedanova et al, 2013). Data on surface and boundary layer wind speed in the potential source regions compared with the threshold for dust mobilisation defined by Chomette et al (1999) as 7-9 m s −1 confirmed potential for dust entrainment.…”
Section: Meteorological and Back Trajectory Datamentioning
confidence: 88%
See 4 more Smart Citations
“…The 700 hPa vector wind fields serve as a good indicator of potential dust transportation to the Caucasus (Shahgedanova et al, 2013). Data on surface and boundary layer wind speed in the potential source regions compared with the threshold for dust mobilisation defined by Chomette et al (1999) as 7-9 m s −1 confirmed potential for dust entrainment.…”
Section: Meteorological and Back Trajectory Datamentioning
confidence: 88%
“…Rototaeva et al, 1998;, characteristics of mineral dust and its provenance was studied in relation to a single dust deposition event, which occurred on Mt. Elbrus on 5 May 2009 (Kokkalis et al, 2012;Shahgedanova et al, 2013). Using this deposition event, Shahgedanova et al (2013) developed a methodology for high temporal (ca.…”
Section: S Kutuzov Et Almentioning
confidence: 99%
See 3 more Smart Citations